Game-specific abilities in elite youth football players: validity and sensitivity to change of subjective coach ratings compared to objectively-assessed data - Niederer, D.; Damm, M.; Grigereit, A.; Banzer, W.; Vogt, L. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: Little is known on the accuracy of coaches` ratings of game-specific physical abilities in elite youth football players. The present study on elite youth football players aims to assess whether: 1) the coaches` subjective assessment of the level of performance of each athlete within the team is in accordance with objectively collected data; and 2) the coaches rate changes in the athletes` performance level accurately or not. METHODS: Data on jumping ability, sprinting speed, change of direction and strength were collected in seven age groups at a football youth academy (N.=150). The diagnostic battery was repeated after seven months (N.=138). Before the second session, the head coaches completed Likert-scaled closed questions on: 1) the importance of running speed and reactive strength components and their relevance to the individual game performance of each of their athletes; 2) the level of performance of their athletes; 3) the change between the first and second performance testing results. Validity and sensitivity of change of their ratings in comparison to the performance data were calculated using analyses of interrelationship. RESULTS: The data of the head coaches showed a low to medium effect size in the agreement with the performance data (Cohen`s W=0.33-0.71). The evaluation of the change in level of performance was poorer (Cohen`s W=0.04-0.2; not statistically significant). CONCLUSIONS: Our results underline that functional/physical testing twice during a season may be crucial for displaying performance levels of elite youth football players. Simple self-reported ratings by the coach may be valid in recent performance level assessment but not for performance changes.